1975
DOI: 10.1161/01.str.6.3.318
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the Young: A Four-Year Study, 1968 to 1972

Abstract: Abstract:Stroke in the Young: A Four-Year Study, 1968 to 1972

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

1981
1981
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Janaki et al reported that an infection with fever preceded cerebral infarction in 10 of their 26 patients under 20 years of age; in keeping with our results infections were mostly of bacterial origin. 25 The best known example of the association of bacterial infection and stroke is infective endocarditis; cerebral infarction is a complication in 10-15% of cases of bacterial endo-carditis.89 In this study two patients (4%) had cerebral infarction due to endocarditis. Both preceding intoxication with alcohols and a high intake of alcohol6 are associated with ischaemic stroke, which agrees with our results.…”
Section: Discussionmentioning
confidence: 66%
“…Janaki et al reported that an infection with fever preceded cerebral infarction in 10 of their 26 patients under 20 years of age; in keeping with our results infections were mostly of bacterial origin. 25 The best known example of the association of bacterial infection and stroke is infective endocarditis; cerebral infarction is a complication in 10-15% of cases of bacterial endo-carditis.89 In this study two patients (4%) had cerebral infarction due to endocarditis. Both preceding intoxication with alcohols and a high intake of alcohol6 are associated with ischaemic stroke, which agrees with our results.…”
Section: Discussionmentioning
confidence: 66%
“…The leading causes of cerebral thrombosis differ greatly between young and old patients. 4 Typically, most cases in young patients are idiopathic, although there are some reports that point out the existence of a background disease. 5 Currently, especially in North America and Europe, UC is considered to be one of the main causes of cerebral thrombosis since Mayeux and Fahn reported that they suspected that UC was associated with cerebral thrombosis aetiologically.…”
Section: Discussionmentioning
confidence: 99%
“…Although the first cases' reports of arterial ischemic stroke (AIS)/acute infantile hemiplegia related to infections issued in the seventies (Roden et al, 1975;Janaki et al, 1975) and though child infections are common, the interest in infectious pediatric strokes had developed recently, probably due to the AIS scarcity (2,4/100,000 US Children per year) (Fullerton et al, 2015). The Vascular Effects of Infection in Pediatric Stroke (VIPS) case control study demonstrated that childhood infections, including varicella zoster virus (VZV), are associated with an increased risk of AIS.…”
Section: Infections and Strokementioning
confidence: 99%